Tax Avoidance And The Auditor's Opinion: The Role Of Uncertainty And Government Ownership (Evidence From The Stock Market Of Iran) - Masoud Taherinia; Mohammad Abdi; Marziyeh Dormishi (Australasian Accounting, Business and Finance Journal, 2022)
The study investigates how market uncertainty and government ownership are associated with tax avoidance and auditor's opinion. The Iranian market is highly volatile and dominated by government ownership, which holds implications on the shareholders' interests. Our research uses a comprehensive data set of 115 listed companies in Tehran Stock Exchange during 2012-2018, using logistic regression technique. We find out that market uncertainty intensifies the positive relationship between tax avoidance and the auditor's modified opinion. The findings indicate that the government presence in the ownership increases the tax avoidance, and hence changes the auditor's report.
Keywords: Uncertainty; Government Ownership; Tax Avoidance; Auditor' s Opinion; Iran